Occurrence of multiple abortions due to Salmonella enterica serovar abortus equi infection - Llorente, L.; Ivanissevich, A.; Camiña, S.; Marco, L.; Vissani, Maria Aldana; Olguin Perglione, Cecilia; Herrera, M.; Barrandeguy, Maria Edith (2017)
Inst.de Virología